Influence of sliding direction relative to layer orientation on tribological performance, noise, and stability in 3D-printed ABS components - Tian, Yang; Zheng, Bohao; Khan, Muhammad; He, Feiyang (Elsevier, 2025)
The tribological performance of 3D-printed ABS components is influenced by layer orientation, yet its effects on friction, wear, noise, and system stability remain underexplored. This study investigates how the angle between sliding direction and layer lines (0°, ± 45°, 90°) impacts these properties in FDM-printed ABS. Pin-on-disc tests (10–20 N loads, 0.314–0.628 m/s speeds) and modeling (FEM for wear and temperature, lumped-parameter for stability) were conducted. The 90° orientation showed the highest coefficient of friction (COF) due to mechanical interlocking but the lowest wear, while the 0° orientation had the lower COF and highest wear from interlayer shear. The −45° orientation produced the most noise due to debris-induced stick-slip, while the 45° orientation generated the least. FEM wear predictions aligned well with experiments (<7 % error), but noise predictions had higher errors (up to 15 %). Increased wear depth raised vibration frequencies, and larger static-kinetic COF differences increased instability.
Keywords: 3D-printed ABS; Layer orientation; Wear; Frictional noise; 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; Mechanical Engineering & Transports; 4014 Manufacturing engineering; 4017 Mechanical engineering